2016
DOI: 10.4236/aim.2016.63023
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Microbial Community at the Interface between Granite Bedrock and Soil Using a Culture-Independent and Culture-Dependent Approach

Abstract: The dissolution of minerals plays an important role in the formation of soils and sediments. In nutrient limiting soils, minerals constitute a major reservoir of bio-essential cations. Of particular interest is granite as it is the major rock type of the continental land mass. Although certain bacteria have been shown to enhance weathering of granite-forming minerals, little is known about the dissolution of granite, at the whole rock scale, and the microbial community involved. In this study, both culture-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Unfortunately, the heterogeneity of the natural environment, the lack of control over changes during even a short sampling period, and the difficulty of finding relevant abiotic controls, make such work challenging. Moreover, although basalt weathering and secondary alteration mineral formation have been widely investigated in the field and in laboratory experiments under abiotic (Gislason and Eugster, 1987;Oelkers and Gislason, 2001;Wolff-Boenisch et al, 2006) and biotic conditions (Wu et al, 2007;Olsson-Francis et al, 2010;Olsson-Francis et al, 2012;Olsson-Francis et al, 2015;Olsson-Francis et al, 2016;Olsson-Francis et al, 2017;Price et al, 2018;Olsson-Francis et al, 2020) these studies have been only over short timeframes (months-years). This makes it difficult, if not impossible, to predict what would happen over years or even over geological time scales when the rock is fully dissolved or more likely, subject to the effects of incongruent dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the heterogeneity of the natural environment, the lack of control over changes during even a short sampling period, and the difficulty of finding relevant abiotic controls, make such work challenging. Moreover, although basalt weathering and secondary alteration mineral formation have been widely investigated in the field and in laboratory experiments under abiotic (Gislason and Eugster, 1987;Oelkers and Gislason, 2001;Wolff-Boenisch et al, 2006) and biotic conditions (Wu et al, 2007;Olsson-Francis et al, 2010;Olsson-Francis et al, 2012;Olsson-Francis et al, 2015;Olsson-Francis et al, 2016;Olsson-Francis et al, 2017;Price et al, 2018;Olsson-Francis et al, 2020) these studies have been only over short timeframes (months-years). This makes it difficult, if not impossible, to predict what would happen over years or even over geological time scales when the rock is fully dissolved or more likely, subject to the effects of incongruent dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mineral microhabitats (mica, basalt, and rock phosphate) contained nutritive elements such as P, K, Na, and Mg, which have been shown to determine and select bacterial communities with distinct structures [ 61 ]. At the same time, mineral weatherability has a prominent impact on microbial communities and can stimulate the growth of effective-weathering bacteria (e.g., β-Proteobacteria) on their surface [ 58 , 59 , 62 , 63 ]. Proteobacteria and Bacteroidetes , as the dominant bacterial phyla in terrestrial and aquatic habitats, are positively related to organic matter [ 64 ] and have been detected on minerals [ 58 , 59 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2010) observed that rocks with porosity of about 20% supported recovery of additional incremental oil from the sandstone core up to 75% [27]. The cores contained elements commonly found in other sandstone reservoirs’ strata [28]. Moreover, the produced water, which was low in salinity and had neutral to slightly alkaline pH, could support microbial growth [5].…”
Section: Discussionmentioning
confidence: 99%